Research about governance models in industrial port zones: the case of Pecém and Marseilles-Fos - Pontes, Denio Igor Silva (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
This article will address governance of industrial port zones (IPZ), a topic that pervades the issue of port management stricto sensu but has a broader scope insofar as it relates to the problem of managing areas that congregate a whole set of physical assets and actors: logistic infrastructures in their multimodality, distribution centers, industrial zones, service providers, port authorities and companies. Throughout this research, we sought to understand and describe the port governance model of two IPZs—the one located in the Brazilian state of Ceará and the other in the Mediterranean Sea, in France. For this, field researches were carried out in both regions. The port of Rotterdam was used as a parameterization model for the two IPZs studied. It was identified that, for an IPZ to be successful, its governance model must assume logistics and industrial sectors as mutually inseparable, preferably with a focus on the region where it is inserted, both when executing management and when seeking economic, social development.